PEMETAAN DAERAH RAWAN LONGSOR BERBASIS SISTEM INFORMASI GEOGRAFIS DALAM UPAYA MITIGASI BENCANA KOTA PALOPO - Hidayat, Wahyu; Sukimin, Ridwan (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2024)
Research on landslide-prone areas based on geographic information systems in disaster mitigation efforts is very important because of the mushrooming of existing development on the outskirts of cities irregularly, resulting in disaster-prone cities. The purpose of the study is to determine the extent of landslide-prone areas through landslide vulnerability mapping so as to optimize disaster mitigation measures. The location of the research study is Palopo City. The research methods used are scoring, weighting and overlay methods for 5 parameters for 5 categories of landslide vulnerability. The results of the analysis of landslide-prone areas in Palopo City show a landslide-prone map with an area that is included in the safe category (2846.71 ha), the safe enough category (4585.60 ha), the vulnerable category (5237.81 ha), the quite vulnerable category (10397.54 ha) and the very vulnerable category (4676.33 ha). The resulting map provides information about landslide-prone areas to the Palopo City government, especially the Palopo City Regional Disaster Management Agency.